The impact of perioperative enteral immunonutrition on frequent clinical outcome in patients with digestive system cancer - Zhang, Wei; Yang, Wenbin; Mo, Zhifeng; Nian, Feng; Huang, Shaomin (Digestive Medicine Research, 2019)
Background: Forepassed trials have indicated that perioperative enteral immunonutrition can improve the clinical outcome for patients with digestive system cancer. The purpose of this study was to evaluate the effect of perioperative enteral immunonutrition on immunity and postoperative complications in patients with digestive system cancer. Methods: A group of 64 patients with digestive system cancer was randomly assigned for perioperative enteral immunonutrition (n=32) or standard enteral nutrition (n=32). The postoperative clinical outcome was assessed based on a clinical index, including postoperative complications, and systemic inflammatory response syndrome (SIRS) duration. Also, the postoperative cellular immunity was compared and evaluated between the two groups. Results: The nutritional therapy of both groups were completed. The occurrence of postoperative infectious complications in the immunonutrition group (6%) was significantly (P=0.020) lower than that of the standard nutrition group (28%). The duration of SIRS in the immunonutrition group (0.77±0.91 days) was significantly shorter than that in the standard nutrition group (1.34±1.46 days) (P=0.012). The postoperative lymphocyte counts and CD4+ T-cells counts significantly declined (P